Nasal Airway Clearance for Bronchiolitis. Issue 6 (November 2018) - Norris, Casey L.; O'Neal, Pamela V.; Adams, Ellise D.; Wyatt, Tami H.
Abstract : Abstract: Bronchiolitis is a leading cause of emergency department visits and hospitalization in the first year of life with estimated costs to the healthcare system in the United States of 1.73 billion annually. The highest rates of admission occur in the first 3 to 6 months of life. Traditional therapies such as bronchodilators and antibiotics have repeatedly been shown to be ineffective. Thickened nasal secretions cause decreased oxygenation, difficulty sleeping, poor feeding, and respiratory distress symptoms. Bronchiolitis guidelines recommend supportive care such as noninvasive nasal airway clearance with saline to clear obstructed airways, improve oxygenation, and promote optimal infant eating and sleeping. Evidence on the safety and efficacy of use of noninvasive nasal airway clearance as supportive care for infants with bronchiolitis in the acute care setting is presented. Abstract : Bronchiolitis is a leading cause of emergency department visits and hospitalization in the first year of life in the United States and has high associated costs. Although the American Academy of Pediatrics has offered clinical practice guidelines for care of infants and children with bronchiolitis, they are not consistently followed in the acute care setting. A review of evidence-based treatment for bronchiolitis is presented.